Empowering Marginalized Families through Client-Centered Counseling: A Sakinah Family Approach in Kampung Topeng, Malang - Rafiqah; Tristiadi Ardi Ardani; Sutrisno; Supriadi; Hosaini; Zohaib Hassan Sain; Lulu Maknunah (Mimbar Agama Budaya, 2026)
This community service program aims to increase the understanding of the people of Kampung Topeng, Malang, about the concept of a harmonious family through a client-centered counseling approach combined with Islamic family values. The methodology used was a Community-Based Participatory Research (CBPR) approach involving 33 residents, community leaders, teachers, and village officials. The intervention involved three client-centered counseling modules tailored for children and adolescents, mothers, and fathers, supported by psycho-religious education, focus group discussions, panel discussions, community competitions, and collaborative reflection. The results show that the program enhanced participants' understanding of the values ​​of love, togetherness, and responsibility within the family. Furthermore, communication and empathy skills among family members showed positive development. Program outputs included training modules and a guidebook on harmonious families. It is therefore recommended that client-centered counseling integrated with Islamic family values ​​and accompanied by ongoing mentoring be adopted to strengthen family resilience in marginalized urban communities.